2001
DOI: 10.1177/030089160108700111
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Cell Proliferation and Angiogenesis in the Prognostic Assessment of Ovarian Granulosa cell Tumors

Abstract: The findings support the importance of proliferative factors, tumor size and histologic patterns as possible prognostic indicators for estimating the biologic behavior of patients with GCT. Unfortunately, angiogenesis did not seem to be a useful determinant parameter of a possible aggressive behavior. However, a longer follow-up period with larger series may be required to assess the value of the parameters in prediction of patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
(4 reference statements)
0
25
4
Order By: Relevance
“…Previous data suggest that mitotic index is a prognostic marker in GCTs (41)(42)(43), but this has not been found in all studies (22,40). We found that VEGF protein expression correlated positively to tumor MVD, independent of tumor size or stage.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Previous data suggest that mitotic index is a prognostic marker in GCTs (41)(42)(43), but this has not been found in all studies (22,40). We found that VEGF protein expression correlated positively to tumor MVD, independent of tumor size or stage.…”
Section: Discussioncontrasting
confidence: 79%
“…As an indirect indicator of tumor angiogenesis, MVD has been shown to be of prognostic significance in ovarian cancer (39), but its role in GCTs is still unknown (40). Previous data suggest that mitotic index is a prognostic marker in GCTs (41)(42)(43), but this has not been found in all studies (22,40).…”
Section: Discussionmentioning
confidence: 99%
“…In other, more benign tumors, no correlation of proliferation and angiogenesis has been reported [12,13] . In paragangliomas, a benign tumor entity with some malignant characteristics, only limited data concerning angiogenesis and proliferation are available.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 An association between the mitotic activity index (MI) of granulosa cell tumor and survival or recurrence has been reported in several studies. 10,12,14,15,55,58,61 In one of these studies, patients whose tumors had a low MI (<3 MI per 10 high-power fields [HPFs]) had a 10-year survival of 70% compared with 37% for those whose tumors had higher MI. 15 In a series, 53 tumors that had <4 mitoses/10 HPFs had a more than 2 times risk of recurrence than did those with <3 mitoses/10 HPFs.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In contrast, other investigators were unable to show that nuclear atypia was of any prognostic significance. 48,61 DNA analyses have indicated that 5% to 20% of granulosa cell tumors are aneuploid. According to some investigators aneuploidy was not a predictor for recurrence, 58,[62][63][64] whereas others found that aneuploidy was associated with high risk for recurrence.…”
Section: Prognostic Factorsmentioning
confidence: 99%